The Effect of Workload, Work Stress, and Work Environment on Employee Performance - Ardyansyah Ardyansyah; Dinar Nur Affini (Universitas Mercu Buana, 2026)
This study aims to analyze the influence of workload, job stress, and the work environment on employee performance at PT. Permata Prima Teknologi. The study population included all 42 employees of the company. A saturated sampling technique was used. The sample size consisted of all 42 employees of PT. Permata Prima Teknologi. This quantitative study used a survey as the data collection method, with a questionnaire using a Likert scale as the research instrument. The data were analyzed using multiple linear regression and processed with Partial Least Squares (PLS) 4.0. The results showed that workload had a significant negative effect on employee performance, job stress had a significant negative effect on employee performance, and the work environment had a significant positive effect on employee performance. Keywords: Workload, Work Stress, Work Environment, Employee Performance